STOCK PRICE MOVEMENT PREDICTION USING SUPERVISED MACHINE LEARNING ALGORITHM: KNIME - Dina Anggraeni; Kris Sugiyanto; Muhammad Irwan Zam Zam; Harry Patria (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2022)
What happened to the money that was invested? Especially in light of the obscene wealth. Obviously, it refers to financial instruments. Let us start with the most basic investment instruments: firm stocks traded on stock exchanges. We have gathered field data from a few manufacturing companies over the last five years (2015–2019), including financial and non-financial data, as well as stock price variance over each year. We used KNIME's machine learning to find the best models for predicting the variance of the stock price in a given year based on the parameters provided. We expect the algorithms to be able to predict which company will return a capital gain for the investor.